Pengaruh Konduktivitas Thermal Busi dan Persentase Octane Booster terhadap Gas Buang Sepeda Motor 108 CC - Luthfi Hadi Ramadhan; Khambali Khambali (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Motorbikes produce exhaust gases that are dangerous for humans over the long term. Motorcycle exhaust gas is produced from incomplete combustion in the combustion chamber. The aim of this research is to anticipate the effects of exhaust gas produced by varying the thermal conductivity of the spark plug electrode and adding a percentage of octane booster to the fuel. This research uses quantitative concepts with experimental methods. Process the data using Microsoft Excel. This research was carried out at idle engine speed. The results show that emissions of CO have decreased significantly. The lowest CO emissions were obtained from a silver spark plug alloy and a 6% octane booster mixture, with a value of 2.09%. HC shows that the exhaust gas emission value has decreased very significantly. The results of HC exhaust gas emissions decreased by 671.66 ppm from the highest, 1121.33 ppm with a standard spark plug alloy and 0% octane booster mixture, to 449.67 ppm with a silver spark plug alloy and 7% octane booster mixture. Meanwhile, CO₂ exhaust emissions have increased. The highest value of CO₂ exhaust emissions are 3.77% with a mixture of silver spark plugs and a mixture of 7% octane booster.